Enabling collaborative GeoVisual analytics: Systems, techniques, and research challenges - García-Chapeton, G. A. (2020)
This article contributes to this objective by reviewing the state‐of‐the‐art of the support for collaborative work in GVA systems and by identifying research challenges and proposing strategies to address them. We conducted a systematic review, resulting in the identification of 13 collaborative systems, 6 distinct collaborative techniques, and 3 research challenges. We conclude that GVA is moving toward more effective support of multidisciplinary and cross‐domain collaborative analysis. However, to materialize this potential, research is needed to improve the support for hybrid collaborative scenarios, cross‐device collaboration, and support for time‐critical and long‐term analysis.